Preparation, characterization, and in vitro evaluation of isoniazid and rifampicin-loaded archaeosomes - Attar, Azade; Bakir, Ceren; Yuce-Dursun, Basak; Demir, Serap; Cakmakci, Emrah; Danis, Ozkan; Birbir, Meral; Ogan, Ayse (WILEY, 2018)
The ability of Archaea to adapt their membrane lipid compositions to extreme environments has brought in archaeosomes into consideration for the development of drug delivery systems overcoming the physical, biological blockades that the body exhibits against drug therapies. In this study, we prepared unilamellar archaeosomes, from the polar lipid fraction extracted from Haloarcula 2TK2 strain, and explored its potential as a drug delivery vehicle. Rifampicin and isoniazid which are conventional drugs in tuberculosis medication were loaded separately and together in the same archaeosome formulation for the benefits of the combined therapy. Particle size and zeta potential of archaeosomes were measured by photon correlation spectroscopy, and the morphology was assessed by with an atomic force microscope. Encapsulation efficiency and loading capacities of the drugs were determined, and in vitro drug releases were monitored spectrophotometrically. Our study demonstrates that rifampicin and isoniazid could be successfully loaded separately and together in archaeosomes with reasonable drug-loading and desired vesicle-specific characters. Both of the drugs had greater affinity for archaeosomes than a conventional liposome formulation. The results imply that archaeosomes prepared from extremely halophilic archaeon were compatible with the liposomes for the development of stable and sustained release of antituberculosis drugs.
Keywords: archaeosome; drug loading; isoniazid; liposome; rifampicin; DRUG-DELIVERY SYSTEMS; FORMULATION PARAMETERS; UNILAMELLAR LIPOSOMES; ORAL DELIVERY; STABILITY; RELEASE; LIPIDS; CARRIERS; MACROPHAGES; MECHANISMS; Biochemistry & Molecular Biology; Pharmacology & Pharmacy